Consequences of Cyberbullying Experienced on Psychological Wellbeing and Appetite Disturbance among University Students - Nugroho, Purwo Setiyo; Samutachak, Bhubate; Jirapramukpitak, Tawanchai; Ghozali; Chamratrithirong, Aphichat (Public Health of Indonesia, 2025)
Background: The rising internet use among Indonesian university students has amplified the risk of cyberbullying, severely affecting their psychological well-being. This issue can trigger anxiety, depression, and self-harm. These psychological issues can lead to negative behaviors, such as appetite disturbance. Promoting awareness, online safety education, mental health support, and collaboration among institutions, families, and policymakers is crucial to creating a safer digital environment. Objective: This study examined the relationship between experiences of cyberbullying, psychological well-being, and appetite disturbance. Method: This study used a cross-sectional design with 700 undergraduate students from Universitas Muhammadiyah Kalimantan Timur, selected via proportional stratified and random sampling from January to March 2024. Participants spanned all academic years. Data were collected using self-administered standard questionnaires. The association between variables was analyzed using Structural Equation Modeling (SEM). Ethical approval was granted by the Institutional Review Board IPSR, Mahidol University, Thailand, and participants received information sheets. Results: The result showed significant associations between cyberbullying experience and psychological well-being and between psychological well-being and appetite disturbance. No significant direct link was found between cyberbullying experience and appetite disturbance. Psychological well-being fully mediated the relationship between cyberbullying experience and appetite disturbance (p-value < 0.000). Coping capacity did not moderate the relationship between cyberbullying experience and psychological well-being. Conclusion: In conclusion, our study highlights the significant association between cyberbullying and psychological well-being and appetite disturbance. It suggests enhancing psychological well-being to mitigate these effects. Future research should refine the study design, expand the population scope, and explore positive coping strategies to improve psychological issues. Keywords: Cyberbullying experience; psychological well-being; appetite disturbance; structural equation model; university students.